Novel Combination of Andrographis paniculata and Phyllanthus niruri to Improve Performance of Laying Hens Infected with Escherichia coli - Sri Hidanah1 , Emy Koestanti Sabdoningrum1,2, Sri Chusniati3 , M. Bagus Kurniawan Saputra4 (Institute of Medico-legal Publications Pvt Ltd, 2021)
The study aims to learn the efficacy combination of Phyllanthus niruri and Androgaphis paniculata toimprove the performance of laying hens infected with Escherichia coli pathogen. Fifty laying hens of IsaBrown strain were randomly divided into 5 treatments, each treatment was divided into 10 replications(n=10). Treatment P0- (control group without infected), P0+ (hens group infected with Avian Pathogenic’sEscherichia coli without given extract), P1 (hens group infected with Avian Pathogenic’s Escherichia coliwith 10% Phyllanthus niruri extract and 30% Androgaphis paniculata), P2 (hens group infected with AvianPathogenic’s Escherichia coli with 20% Phyllanthus niruri extract and 20% Androgaphis paniculata) andP3 (hens group infected with Avian Pathogenic’s Escherichia coli with 30% Phyllanthus niruri extract and10% Androgaphis paniculata). Performances observed were feed consumption, Hen Day Production, eggsweight and feed conversion. Data analyzed by ANOVA and tested with the F test. The feed consumptionshowed in P1 was different from P3, P2, P0+ and P0-, P1 was different from P2 but not with P3, P0+, andP0- showed significantly different in each treatment. In P3 showed no differences with all treatments. Theeggs weight showed different in P0+ for all treatments, while the other treatments in P1, P2, P3 and P0-showed no differences. The feed conversion showed in P0+ was different for all treatments, while othertreatments showed no difference. P0+ treatment compared to (P0-, P1, P2) was significantly different, P0+treatment compared to P3 treatment was not significantly different, between P3 and P1 treatment was notsignificantly different, and between P1 and P2 with P0- was not significantly different, also between P3 withP2 and P0- treatments was significantly different. Supply of P. niruri extract. and A. paniculata in layinghens can improve the performance of laying hens infected with Escherichia coli pathogen.